Utility Of Rasayana In Present Era - Kushwaha, Ashwini Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Science has made incredible progress in the twenty-first century. At the same time, the world has come a long way in the field of technical knowledge and new methods of medicine are also developing in the health system, but it is also a bitter truth that health related services are getting costlier day by day. Human life has become very dynamic in today’s race. Currently human has everything but due to scarcity of time we are not able to pay attention to our health. As a result human is suffering from various types of mental and physical diseases like anxiety, depression, blood pressure, diabetes etc. In such a circumstances, Rasayana therapy described in Ayurvedic literature can prove to be very beneficial for the human society. Rasayana is one of the eight branches of Ayurveda and also known as Rejuvenation therapy. The principal aim of the Rasayana is to provide accelerated and appropriated nutrition leading to improved biological competence of the body that leads to series of secondary attributes like prevention of aging, longevity and promotion of mental and physical health.